2021
DOI: 10.31235/osf.io/7d8gc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the Impact of COVID-19 Pandemic on Vulnerable Populations in Bangladesh

Abstract: COVID-19 has affected all classes of people over the world in many ways. In major cases, the impact of COVID-19 on vulnerable group of people is overlooked though they are the major part of the society. Thus, this paper aims at investigating the impacts of COVID-19 on vulnerable people in Bangladesh intensively. Using literature review and case studies, this paper finds some interesting findings. The daily income of poor classes of people like day laborers, Rickshaw pullers, transport workers and so on reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Through these the students and teachers gaining new experiences on Information Technology that is counting as a development of our country. Studies have already demonstrated that online mode of teaching will enable the educational institutions to teach 15-18% additional students at the same cost, as a report of Daily Star [5].…”
Section: K Use Of Online Classes As a Way Of Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through these the students and teachers gaining new experiences on Information Technology that is counting as a development of our country. Studies have already demonstrated that online mode of teaching will enable the educational institutions to teach 15-18% additional students at the same cost, as a report of Daily Star [5].…”
Section: K Use Of Online Classes As a Way Of Solutionmentioning
confidence: 99%
“…For the Covid-19 pandemic, demand for private tutors dropped significantly [5]. That's why many students who have worked as private tutors are passing miserable days.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The government of Bangladesh has declared an incentive package for early economic recovery that is needed for businesses to survive the pandemic. 12 The unprecedented COVID-19 pandemic has become a global burden disrupting peoples' quality of life. Students are an important cohort of a country, and their mental health during this pandemic has been recognized as a concerning issue.…”
Section: Introductionmentioning
confidence: 99%